P645T2-mapping cardiac MRI for in vivo quantification of myocardial area-at-risk. (15th July 2014) - Dongworth, RK; Campbell-Washburn, AE; Roberts, T; Yellon, DM; Lythgoe, MF; Hausenloy, DJ
Abstract: Purpose: Novel therapeutic strategies are required to protect the heart against acute ischaemia-reperfusion injury (IRI). Assessing their cardioprotective efficacy requires measurement of infarct size (IS) and the "area-at-risk (AAR). T2-weighted cardiac magnetic resonance imaging (cMR) can delineate the AAR in vivo by detecting areas of oedema following IRI. However, clinical studies suggest that some cardioprotective interventions can reduce the extent of oedema measured by T2-weighted cMR, thereby affecting AAR measurement by this cMR method. We sought to investigate the validity of T2-mapping cMR for in vivo AAR quantification in hearts protected by ischaemic preconditioning (IPC). Methods: B6SV129 mice were subjected to in vivo acute IRI comprising LAD ligation for 30 minutes followed by 72 hours reperfusion. IPC-treated animals were subjected to a standard cardioprotective protocol of 5 minutes ischaemia and 5 minutes reperfusion prior to the main ischaemic insult. Following 3 days reperfusion, mice underwent cMR consisting of late-gadolinium enhancement and T2-mapping for assessment of infarct size and putative AAR, respectively. Immediately following cMR, hearts were excised and subjected to histological staining using triphenyl tetrazolium chloride and Evan's blue for infarct size and AAR, respectively. Assessment of cMR quantifications was performed by comparison with equivalent histological staining of left ventricular myocardial slices for infarct size (IS/LV%) and AAR (AAR/LV%). Results: cMR T2-maps of the myocardium in control and IPC-treated mice showed clearly defined regions of elevated T2-signal in spatially distinct regions of the myocardium. Comparison of T2-maps and histological staining for each slice demonstrated good agreement in the spatial localisation of AAR judged by T2-cMR and histology. Quantification of AAR from T2-maps showed no significant difference to AAR quantified by 'gold-standard' histological staining in control mice (AAR/LV% control: T2-cMR 60.4±2.4; versus histology 64.3±2.5: n=6, p>0.05). Importantly, T2-cMR significantly underestimated AAR in in IPC treated mice (AAR/LV% IPC: T2-cMR 46.0±13.2; versus histology 59.8±7.8: n=10, *p<0.05). Conclusions: Although the T2-mapping cMR protocol developed in here permits accurate quantification of myocardial area-at-risk in control mice following IRI; crucially, IPC significantly reduced the area of oedema and thus invalidated AAR measurement by T2-cMR in this model in the presence of IPC. Further investigation of the validity of T2-cMR for in vivo AAR assessment is now required for other therapeutic interventions.